Erections of Changa gen. nov. and Songga gen. nov. of Aolina (Hemiptera: Cicadidae: Cicadinae: Dundubiini) with taxonomic notes and a synonymization - Lee, Young June (Zootaxa, 2016)
Two new genera, Changa gen. nov. and Songga gen. nov., are erected in the subtribe Aolina Boulard, 2012, with the designations of Cosmopsaltria sita Distant, 1881 and Pomponia scitula Distant, 1888 as the type species, respectively. Khimbya sita (Distant, 1881) becomes Changa sita (Distant, 1881) comb. nov. Haphsa scitula (Distant, 1888) becomes Songga scitula (Distant, 1888) comb. nov. Haphsa jsguillotsi (Boulard, 2005) is transferred to Changa to become Changa jsguillotsi (Boulard, 2005) comb. nov. Haphsa stellata Lee, 2009 syn. nov. is synonymized with Changa sita. Haphsa sulaeyai (Boulard, 2005) is transferred to Macrosemia Kato, 1925 to become Macrosemia sulaeyai (Boulard, 2005) comb. nov. A revised key to the genera of Aolina is provided.